DISCONTOOLS: Identifying gaps in controlling bovine spongiform encephalopathy. (10th August 2017) - Simmons, M.; Ru, G.; Casalone, C.; Iulini, B.; Cassar, C.; Seuberlich, T.
Summary: This article summarizes the 2016 update of the DISCONTOOLS project gap analysis on bovine spongiform encephalopathy (BSE), which was based on a combination of literature review and expert knowledge. Uncertainty still exists in relation to the pathogenesis, immunology and epidemiology of BSE, but provided that infected material is prohibited from entering the animal feed chain, cases should continue to decline. BSE does not appear to spread between cattle, but if new strains with this ability appear then control would be considerably more difficult. Atypical types of BSE (L‐BSE and H‐BSE) have been identified, which have different molecular patterns and pathology, and do not display the same clinical signs as classical BSE. Laboratory transmission experiments indicate that the L‐BSE agent has zoonotic potential. There is no satisfactory conclusion regarding the origin of the BSE epidemic. C‐BSE case numbers declined rapidly following strict controls banning ruminant protein in animal feed, but occasional cases still occur. It is unclear whether these more recent cases indicate inadequate implementation of the bans, or the possibility that C‐BSE might occur spontaneously, as has been postulated for H‐ and L‐BSE. All of this will have implications once existing bans and levels of surveillance are both relaxed. Immunochemical tests can only be applied post‐mortem. There is no immunological basis for diagnosis in the live animal. All aspects of disease control are expensive, particularly surveillance, specified risk material removal and feed controls. There is pressure to relax feed controls, and concurrent pressure from other sources to reduce surveillance. While the cost benefit argument can be applied successfully to either of these approaches, it would be necessary to maintain the ban on intraspecies recycling and some baseline surveillance. However, the potential risk is not limited to intraspecies recycling; recycling with cross‐species transmission may be an ideal way to select or/and modify properties of transmissible spongiform encephalopathies agents in the future.